Analysis of High-Frequency Behavior of AlGaN/GaN HEMTs and MIS-HEMTs under UV Illumination. (3rd May 2021) - Chen, Kun-Ming; Lin, Chuang-Ju; Nagarajan, Venkatesan; Chang, Edward Yi; Lin, Chao-Wen; Huang, Guo-Wei
Abstract : The high-frequency characteristics of AlGaN/GaN high-electron-mobility transistors (HEMTs) and metal-insulator-semiconductor HEMTs (MIS-HEMTs) are investigated under ultraviolet (UV) radiation with 365 nm wavelength. When HEMTs and MIS-HEMTs are illuminated with an UV source, their drain currents increase apparently owing to the generated photocurrent. Nevertheless, they show different high-frequency response to the UV light. For HEMTs, the peak cutoff frequency (fT ) and maximum oscillation frequency (fmax ) of illuminated devices are 20% and 10% higher than those in dark condition, respectively, owing to the increased transconductance. For MIS-HEMTs, however, their high-frequency performances are degraded when transistors are subject to light exposure. The degradations of peak fT and fmax are around 3.7% and 18%, respectively. The small-signal model parameters relevant to the high-frequency characteristics were extracted to explain these phenomena. Additional trapped charges in the SiN gate dielectric induced by UV light would be responsible for the degraded high-frequency parameters in illuminated MIS-HEMTs. These experimental results are important for designing a suitable GaN-based HEMT for optoelectronic applications.